THE EFFECT OF IMPLEMENTING DATA-BASED LEARNING MODELS ON EMPLOYEE PERFORMANCE IN STEAM POWER PLANT COMPANIES - Satrio Fajar Pangestu; Ibnu Farid; Gaguk Triono; Danny Dwi Rachmanto (OIKONOMIA: Journal of Economics and Management Science, 2024)
This research aims to explore the effect of implementing a data-based learning model on employee performance at the Steam Power Plant Company, a service company. The research method used was a quasi-experimental design with two groups, namely the experimental group that received data-based learning model intervention and the control group that did not receive the intervention. Data was collected through pre-test and post-test, and analyzed using t-test, ANOVA test, and regression test. The results show that the data-based learning model is effective in improving employee performance, with significant improvements seen in data analysis, problem solving, decision making, and communication skills. The implications of this research include increasing productivity, competitiveness and employee retention, as well as strengthening the company's reputation as a workplace that supports employee development